PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BADAN USAHA MILIK DESA PERSPEKTIF MAQASHID SYARIAH DI DESA SEBAYAN KECAMATAN SAMBAS - Ridawati; Budi Iswanto; Wulan Purnamasari (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
BUMDes in the last few years is indeed a subject of conversation, not only by ordinary people but also among researchers and students. It is understandable, because the existence of BUMDes has a strategic role in the society especially in rural areas. If observed carefully the nature of BUMDes not solely as an economic institution of a commercial nature, but also as a means to improve the welfare of society. This study aims to Describe the business units BUMDes Joint Venture which is located in the Village of Sebayan Kecamatan Sambas. Analyze the role of BUMDes in the economic empowerment of the community in the village of Sebayan Kecamatan Sambas Kabupaten Sambas, which are then reviewed from the perspective of Maqasid Shariah. The research method used in this research is qualitative research this type of research is field research where the data collection using interviews, observation and documentation. While for data analysis techniques, namely the reduction of data presentation of data and drawing conclusions as for checking the validity of data is by using triangulation of sources. The results of this research can be known that: the farm Shop, Organic Farm and kos-kosan. The existence of BUMDes is perceived to be very beneficial for the community so that the life of the Village community more prosperous and increasing in terms of the economy. In view of the maqasid syariah BUMDES a Joint Effort Village Sebayan has fulfill some point maqasid shariah, namely the preservation sense, guard treasure, and environmental safeguards.